2008
DOI: 10.2747/1539-7216.49.5.523
|View full text |Cite
|
Sign up to set email alerts
|

China's Dynamic Industrial Sector: The Automobile Industry

Abstract: Two leading Beijing-and Singapore-based economic geographers examine the recent developments and spatial change in China's automobile industry (currently the world's third largest). The paper covers changes in market share among major automobile transnational corporations as well as domestic assemblers; industrial restructuring in the form of product diversification (SUVs to hybrid cars) and production concentration; the massive increase in exports of motor vehicles; and the rise of new automobile production c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…First, rapid economic growth in several large developing countries has led to increases in purchasing power and a growing demand for private cars. A perceived large future market potential in these countries (e.g., China, India, and Brazil) prompted foreign automotive TNCs to build production capacity or form joint ventures with domestic vehicle producers there (e.g., Liu and Yeung 2008; Liu and Dicken 2006; Van Biesebroeck and Sturgeon 2010). Second, peripheral areas surrounding the traditional core areas of automotive production have become attractive because they combine lower production costs; geographic proximity to large and affluent core markets; and the advantages of regional economic blocs, such as the European Union (EU) and the North American Free Trade Agreement.…”
mentioning
confidence: 99%
“…First, rapid economic growth in several large developing countries has led to increases in purchasing power and a growing demand for private cars. A perceived large future market potential in these countries (e.g., China, India, and Brazil) prompted foreign automotive TNCs to build production capacity or form joint ventures with domestic vehicle producers there (e.g., Liu and Yeung 2008; Liu and Dicken 2006; Van Biesebroeck and Sturgeon 2010). Second, peripheral areas surrounding the traditional core areas of automotive production have become attractive because they combine lower production costs; geographic proximity to large and affluent core markets; and the advantages of regional economic blocs, such as the European Union (EU) and the North American Free Trade Agreement.…”
mentioning
confidence: 99%
“…Geographical researchers in China are mainly interested in the production and manufacturing of automobiles, as opposed to their consumption. Therefore, they focus on the development of automotive industry in the country, such as the spatial pattern of car manufacturers or auto industrial cluster (Liu and Yeung, 2008;Wang and He, 2009;Liu and He, 2011;Zhao et al, 2014), areal division of auto industrial chain (Li and Gu, 2010) and spatial evolution of auto industry (Huang and Zhang, 2014). The reason why studies on spatial pattern of car sales are scarce is likely that the data of car sales at such a middle or micro level are usually not accessible in China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many of the Japanese FIEs are long‐established brands such as Toyota, Nissan, Hitachi and Honda, instead of those adopting the OEM or ODM business model. As several major Japanese automobile makers settled in Guangzhou, the city has become the second‐ranking city in China in terms of automobile production in 2007 (Liu & Yeung ). Geographical location, proximity to market, and availability of services provided by the local governments are regarded as important reasons behind the initial location of Japanese FIEs in Guangdong.…”
Section: Spatial Dynamics and Redistribution Of Fdi From Different Somentioning
confidence: 99%
“…One of the most important driving forces for the expansion is the boom of the domestic auto market. From 2000 to 2007, the annual growth rate of motor production in China was 23.5% while the number of passenger cars on the road in China has risen significantly (Liu & Yeung ). Seventy seven per cent of the studied Japanese FIEs reported that closeness to market is the most crucial factor underlying their locations.…”
Section: Spatial Dynamics and Redistribution Of Fdi From Different Somentioning
confidence: 99%